Locomotor training with adjuvant testosterone preserves cancellous bone and promotes muscle plasticity in male rats after severe spinal cord injury. Issue 5 (4th December 2019) - Yarrow, Joshua F.; Kok, Hui Jean; Phillips, Ean G.; Conover, Christine F.; Lee, Jimmy; Bassett, Taylor E.; Buckley, Kinley H.; Reynolds, Michael C.; Wnek, Russell D.; Otzel, Dana M.; Chen, Cong; Jiron, Jessica M.; et al.
Abstract: Loading and testosterone may influence musculoskeletal recovery after spinal cord injury (SCI). Our objectives were to determine (a) the acute effects of bodyweight‐supported treadmill training (TM) on hindlimb cancellous bone microstructure and muscle mass in adult rats after severe contusion SCI and (b) whether longer‐term TM with adjuvant testosterone enanthate (TE) delivers musculoskeletal benefit. In Study 1, TM (40 min/day, 5 days/week, beginning 1 week postsurgery) did not prevent SCI‐induced hindlimb cancellous bone loss after 3 weeks. In Study 2, TM did not attenuate SCI‐induced plantar flexor muscles atrophy nor improve locomotor recovery after 4 weeks. In our main study, SCI produced extensive distal femur and proximal tibia cancellous bone deficits, a deleterious slow‐to‐fast fiber‐type transition in soleus, lower muscle fiber cross‐sectional area (fCSA), impaired muscle force production, and levator ani/bulbocavernosus (LABC) muscle atrophy after 8 weeks. TE alone (7.0 mg/week) suppressed bone resorption, attenuated cancellous bone loss, constrained the soleus fiber‐type transition, and prevented LABC atrophy. In comparison, TE+TM concomitantly suppressed bone resorption and stimulated bone formation after SCI, produced near‐complete cancellous bone preservation, prevented the soleus fiber‐type transition, attenuated soleus fCSA atrophy, maintained soleus force production, and increased LABC mass. 75% of SCI+TE+TM animals recovered voluntary over‐ground hindlimb stepping, while no SCI and only 20% of SCI+TE animals regained stepping ability. Positive associations between testosterone and locomotor function suggest that TE influenced locomotor recovery. In conclusion, short‐term TM alone did not improve bone, muscle, or locomotor recovery in adult rats after severe SCI, while longer‐term TE+TM provided more comprehensive musculoskeletal benefit than TE alone. Abstract : In our rodent severe contusion spinal cord injury (SCI) model, a regenerative rehabilitation strategy combining pharmacologic testosterone with bodyweight‐supported treadmill training (TE+TM) produced more comprehensive muscle and bone recovery than TE alone. 75% of TE+TM animals also regained voluntary over‐ground hindlimb stepping, while no SCI and only 20% of SCI+TE recovered this ability.